Importance of NF-κB in rheumatoid synovial tissues: in situ NF-κB expression and in vitro study using cultured synovial cells. Issue 7 (1st July 2001) - Yamasaki, S; Kawakami, A; Nakashima, T; Nakamura, H; Kamachi, M; Honda, S; Hirai, Y; Hida, A; Ida, H; Migita, K; Kawabe, Y; Koji, T; et al.
Abstract : OBJECTIVES: To examine whether inhibition of NF-κB induces apoptosis of human synovial cells stimulated by tumour necrosis factor α (TNFα), interleukin 1β (IL1β), and anti-Fas monoclonal antibody (mAb). METHODS: The expression of proliferating cell nuclear antigen (PCNA), NF-κB, and the presence of apoptotic synovial cells were determined in synovial tissues. Apoptosis of cultured synovial cells was induced by inhibition of NF-κB nuclear translocation by Z-Leu-Leu-Leu-aldehyde (LLL-CHO). The activation of caspase-3 and expression of XIAP and cIAP2 in synovial cells in LLL-CHO induced apoptosis was also examined. RESULTS: Abundant PCNA+ synovial cells were found in rheumatoid arthritis (RA) synovial tissue, though a few apoptotic synovial cells were also detected in the RA synovial tissues. Nuclear NF-κB was expressed in RA synovial cells. Electrophoretic mobility shift assay showed that treatment of cells with TNFα or IL1β significantly stimulated nuclear NF-κB activity. A small number of apoptotic synovial cells expressing intracellular active caspase-3 were found after treatment of cells with LLL-CHO. Although treatment of RA synovial cells with TNFα or IL1β alone did not induce apoptosis, apoptosis induced by LLL-CHO and caspase-3 activation were clearly enhanced in TNFα or IL1β stimulated synovial cells compared with unstimulated synovial cells. Furthermore, induction of apoptosis of synovial cells with caspase-3 activation by anti-Fas mAb was clearly increased by LLL-CHO. The expression of cIAP2 and XIAP in synovial cells may not directly influence the sensitivity of synovial cells to apoptosis induced by LLL-CHO. CONCLUSION: The results suggest that NF-κB inhibition may be a potentially important therapeutic approach for RA by correcting the imbalance between apoptosis and proliferation of synovial cells in RA synovial tissue.